Navigating HOPE (Hypermobile Online Pain managemEnt): Perspectives and Experiences From People With Hypermobile Ehlers–Danlos Syndrome or Hypermobility Spectrum Disorder on a Condition‐Specific Online Pain Management Programme - Min Tze Chew; Emre Ilhan; Sarah Dennis; Leslie L. Nicholson; Sarah Kobayashi; Cliffton Chan (Health Expectations)
ABSTRACT Introduction The Hypermobile Online Pain managemEnt (HOPE) programme is a stakeholder informed intervention adopting the biopsychosocial pain approach, specifically for people with hypermobile Ehlers–Danlos Syndrome (hEDS) and hypermobility spectrum disorder (HSD) experiencing pain. The programme topics included were based on a modified Delphi of a large sample of stakeholders: people with hEDS/HSD and healthcare practitioners who are experienced with managing these conditions. Programme feasibility, acceptability and appropriateness were previously evaluated quantitatively in a pilot randomised controlled trial, but the in‐depth experiences and perceptions of participants who engaged with the programme is unknown. Methods Qualitative study. 1:1, semi‐structured online interviews of participants who took part in the HOPE programme. Data was analysed using an inductive thematic analysis approach as described by Braun and Clark. Results Twelve participants were interviewed; 91% were female, mean age 38.1 (SD 9.1). Four themes emerged: (1) The biopsychosocial approach to understanding pain used in the HOPE programme was acceptable and appropriate, (2) benefits of the programme were stronger for those who were newer on their hEDS/HSD journey, (3) self‐guided reflections included in the programme required headspace and personal meaning and (4) participants desired more adaptable content and programme functionality. Additionally, participants gave suggestions on how to improve the content, adherence and engagement to the programme. Conclusion The HOPE programme was considered feasible, acceptable and appropriate for people with hEDS/HSD. The four themes and suggestions from our study findings will be used to refine subsequent versions and large‐scale trials of the HOPE programme, as well as provide translatable insights for other online interventions for hEDS/HSD or similar complex, chronic multisystemic conditions. Patient or Public Contribution A large community of hEDS/HSD patients' and healthcare providers' input were obtained from a two‐staged online Delphi from a prior study. This approach was preferred to capture the greatest amount of feedback from a diverse international voice. Via the Delphi study, they provided suggestions for content topics and consensus on what they felt were important to include in a hEDS/HSD specific online pain management programme, as well as programme parameters (e.g., duration and frequency of programme; healthcare provider telehealth component; types of learning activities).